EFEKTIVITAS PENERAPAN MODUL MIKROBIOLOGI HASIL PERTANIAN BERVISI PROBLEM BASED LEARNING KELAS X DI SMK N 1 BAWEN - Mubtadiah, Chulia; Bintari, Siti Harnina; Mubarok, Ibnul (Journal of Biology Education, 2014)
LearningÂ  context in vocational schools involves a process of acquiring knowledge, lifeskill, skills and attitudes regarding competency to do a task or job. Teaching materials are chosen not only describe the material in detail , but also provide learning experiences according to the learnerâs learning abilities. Studentâs critical thinking skills can be developed through contextual learning as learning that emphasizes problem solving (Problem Based Learning). This research aims to develop a valid and effective product of the learning modules in the SMK. The design was applied in Research and Development. Initial sample test use purposive random sampling method using a test hiatus. Learning results obtained in field trials achieve implementation classical completeness of 92.30% for X AHP A, 94.73% for X AHP B and 97.36% for X AHP C at a predetermined value KKM is 75.Â Konteks pembelajaran di sekolah menengah kejuruan melibatkan proses memperoleh pengetahuan, kecakapan, keterampilan dan sikap yang berkenaan kompetensi menyelesaikan tugas atau pekerjaan. Bahan ajar dipilih tidak hanya sekedar memaparkan materi secara terperinci, namun juga memberi pengalaman belajar menurut kemampuan belajar peserta didik. Kemampuan berpikir kritis peserta didik dapat dibangun melalui pembelajaran kontekstual seperti pembelajaran yang mengedepankan penyelesaian masalah (Problem Based Learning). Penelitian ini bertujuan menguji keefektifan modulÂ  dalam proses pembelajaran di SMK. Desain yang diterapkan dalam penelitian adalah One Shot Case Study sebanyak 3 kelas di jurusan Agribisnis Hasil Pertanian. Hasil belajar yang diperoleh pada uji pelaksanaan lapangan mencapai ketuntasan 92.30% untuk X AHP A, 94.73% untuk X AHP B dan 97.36% untuk X AHP C pada nilai KKM yang telah ditetapkan yaitu 75.